The impact of TikTok social media influencers on consumer behavior: a systematic literature review - Tian, Zhuang; Wan Abas, Wan Anita; Ahmad Ghazali, Akmar Hayati; Zhao, Xianlu (Redfame Publishing, 2025)
Research on TikTok social media influencers and consumer behavior has expanded rapidly in recent years. However, the existing literature remains fragmented, regionally concentrated, and theoretically inconsistent. Given TikTok’s growing influence in shaping consumer decision-making, this study conducts a systematic literature review to critically synthesize current knowledge and address gaps in research topics, theoretical models, key variables, and conceptual frameworks. Guided by the PRISMA methodology, this review analyzes 32 peer-reviewed journal articles published between 2019 and March 2025. Using the Antecedents-Decisions-Outcomes (ADO) framework, the study develops a structured model illustrating how influencer characteristics affect consumer decisions and behavioral outcomes on TikTok. The findings reveal a diverse range of antecedents-including credibility, emotional appeal, platform engagement, and parasocial relationships-that influence decision-related variables such as attitude, trust, and impulsivity. These decisions subsequently lead to outcomes such as purchase intention, actual purchases, impulsive buying, travel intentions, and long-term engagement or brand loyalty. While established theories such as the Source Credibility Model and the Theory of Reasoned Action (TRA) are widely employed, newer frameworks are emerging to better suit TikTok’s dynamic and participatory environment. The proposed model offers strategic insights for marketers and brands aiming to improve campaign effectiveness, strengthen consumer trust, and drive meaningful engagement through TikTok influencer marketing.